Social Transformation and Symbolic Interaction Around UIN Sunan Ampel Surabaya Based on Sociological Approach - Isbil Wardatun Najiah; Luthfi Hidayatu Yasma (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This research aims to analyze the social transformation and symbolic interactions that occur around the State Islamic University (UIN) Sunan Ampel Surabaya. A sociological approach is used to understand this phenomenon in a broader social and cultural context. The research methods used were in-depth interviews with various related parties, participatory observation, and content analysis. The results of this research indicate that there have been significant social changes around UIN Sunan Ampel Surabaya. This social transformation involves various factors, such as technological developments, changes in social structure, and cultural dynamics. Symbolic interaction also plays an important role in this transformation process, where the symbols and meanings associated with UIN Sunan Ampel Surabaya form diverse social interaction patterns. In the context of a sociological approach, this research reveals the importance of understanding the role of educational institutions, such as UIN Sunan Ampel Surabaya, in changing patterns of social interaction and influencing social transformation in their surroundings. This research also provides insight into how the symbols and meanings associated with UIN Sunan Ampel Surabaya can shape social identity and interaction patterns on and around campus